Implications Emergence Platform Tiktok Shop Against Regulations Trade in Indonesia (Analysis of Minister of Trade Regulation No.31 of 2023) - Pohan, Siti Aisyah; Rizal, M. (Fakultas Syariah INSURI Ponorogo, 2024)
The rapid development of technology has significantly impacted various aspects of human life, one of which is TikTok Shop, a social trading platform in Indonesia that has triggered legal issues and disrupted the e-commerce landscape. This research explores the analysis of Permendag No. 31 of 2023 concerning trade regulations in Indonesia. The method used in this study is a qualitative research method that analyzes the regulations issued by the Minister of Trade, alongside several journals that form the basis of the research. The data in this research article identifies the main legal issues contributing to the platform, including legal protection provided to MSMEs, taxation issues, and the regulations of the Minister of Trade. The results of this research indicate that electronic commerce business actors intending to provide services using an electronic system must register and apply for a commercial transaction permit via the electronic system. One of the government's primary objectives in requiring e-commerce players to register with the electronic system is to protect all stakeholders, including economic actors and consumers. The TikTok Shop feature is one of the reasons the Minister of Trade issued this regulation, as it does not yet have official permission to operate as an e-commerce platform. By complying with existing regulations, the business community can take advantage of the opportunities offered by the e-commerce ecosystem and contribute to building a fair and legal digital business environment.